Erratum: In the article by Vladimir Miloradović, Dušan Nikolić, Miodrag Srećković, Ivana Đokić Nikolić. Extremly tortuous coronary arteries - when optical coherence tomography and fractional flow reserve did not help us much / ekstremno tortuozne koronarne arterije - kada optička koherentna tomografija i frakciona rezerva protok ne pomažu mnogo. Vojnosanit pregl 2018; 75(1): 100-103, https://doi.Org/10.2298/VSP160316213M - Editorial (Vojnosanitetski Pregled)
In the article by Vladimir Miloradović, Dušan Nikolić, Miodrag Srećković, Ivana Djokić Nikolić. Extremly tortuous coronary arteries - When optical coherence tomography and fractional flow reserve did not help us much / Ekstremno tortuozne koronarne arterije - kada optička koherentna tomografija I frakciona rezerva protok ne pomažu mnogo. Vojnosanit Pregl 2018; 75(1): 100-103, https://doi.org/10.2298/VSP160316213M two authors (Vladimir Miloradović and Miodrag Srećković) have additional affiliation. The list of the authors and their affiliations should have read: Vladimir Miloradović*†, Dušan Nikolić*, Miodrag Srećković*†, Ivana Djokić Nikolić*. Clinical Centre of Kragujevac, Cardiology Clinic, *Department of Interventional Cardiology, Kragujevac, Serbia; University of Kragujevac, †Faculty of Medical Sciences, Kragujevac, Serbia. Link to the corrected article 10.2298/VSP160316213M